Potencjalne zagrożenia związane z prowadzeniem działalności bancassurance przez bank - Swacha-Lech, Magdalena (Potential Threats Related to Bancassurance Activities of Banks, 2008)
The aim of the article is presentation of threats relating to banks engaged in bancassurance activity. Indicated threats are shown in four following groups: 1) threats relating to risk accumulation, 2) threats relating to partner selection, 3) threats relating to bancassurance organization, 4) threats as a result of change environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 146-161